Optimization of Counterfort Retaining Wall Structure with Shear Key using Metaheuristic Method - Gogot Setyo Budi; Joel Glenn Chandra; Bryan Saputra Ongkowardhana; Willy Husada (Civil Engineering Dimension, 2024)
This paper presents the optimization work to obtain the most economical of counterfort retaining wall structure with shear key attached at its base using metaheuristic method. The metaheuristic algorithm is a global optimization method that can be used to find the optimum solution of complex problems. In this research, optimization is carried out using the Particle Swarm Optimization (PSO) and Symbiotic Organisms Search (SOS) methods. This research utilizes a retaining wall sitting on stiff clay layer subjected to ten (10) m of granular soil of backfill. The scope of the study is limited to the material cost, that consists of the cost of concrete and reinforcement bars, of the counterfort retaining wall with shear key. The results show that the SOS algorithm resulted a lower cost and relatively faster in obtaining optimum retaining wall design compared to that of the PSO algorithm.